An experience of collective construction of a self-evaluation instrument in the service of medical education grounded in the National Curricular Guidelines and based on the More Doctors Program - Lemes De Sordi, Mara Regina; Cavalcanti Vaz Mendes, Geisa do Socorro; Cyrino, Eliana Goldfarb [UNESP]; Fronza Alexandre, Fabiola Lucy; Manoel, Cassia Marisa [UNESP]; Miranda Lopes, Cesar Vinicius (Univ Estadual Paulista-unesp, 2020)
This article presents the experience of construction of a self-evaluation instrument focusing on the new National Curricular Guidelines (DCN) for Medicine programs, published in 2014, which ground the pedagogical projects of medical schools' courses created in the context of the More Doctors Program. The methodology of construction of this tool was based on collective work and interprofessionality and involved different perspectives and types of knowledge in its conception, in the definition of dimensions, and in the election of indicators. After many negotiation rounds, the instrument was validated and has been used in medicine courses of Brazilian federal universities in a formative perspective of evaluation, favoring the identification of strengths and weaknesses of the courses' pedagogical projects, emphasizing the requirements of an education in and for the Brazilian National Health System (SUS). The inductive strength of the evaluation contributed to the affirmation of ideas-forces that are strategic to the implementation of counter-hegemonic processes in medical education.
Keywords: Self-evaluation; National Curricular Guidelines; Medical education; Education for SUS; More Doctors Program